Review of therapeutic agents for burns pruritus and protocols for management in adult and paediatric patients using the GRADE classification - Ioannis Goutos; Maria Clarke; Clara Upson; Patricia M. Richardson; Sudip J. Ghosh (Indian Journal of Plastic Surgery)
To review the current evidence on therapeutic agents for burns pruritus and use the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) classification to propose therapeutic protocols for adult and paediatric patients. All published interventions for burns pruritus were analysed by a multidisciplinary panel of burns specialists following the GRADE classification to rate individual agents. Following the collation of results and panel discussion, consensus protocols are presented. Twenty-three studies appraising therapeutic agents in the burns literature were identified. The majority of these studies (16 out of 23) are of an observational nature, making an evidence-based approach to defining optimal therapy not feasible. Our multidisciplinary approach employing the GRADE classification recommends the use of antihistamines (cetirizine and cimetidine) and gabapentin as the first-line pharmacological agents for both adult and paediatric patients. Ondansetron and loratadine are the second-line medications in our protocols. We additionally recommend a variety of non-pharmacological adjuncts for the perusal of clinicians in order to maximise symptomatic relief in patients troubled with postburn itch. Most studies in the subject area lack sufficient statistical power to dictate a ‘gold standard’ treatment agent for burns itch. We encourage clinicians to employ the GRADE system in order to delineate the most appropriate therapeutic approach for burns pruritus until further research elucidates the most efficacious interventions. This widely adopted classification empowers burns clinicians to tailor therapeutic regimens according to current evidence, patient values, risks and resource considerations in different medical environments.